2012
DOI: 10.1007/s10681-012-0676-2
|View full text |Cite
|
Sign up to set email alerts
|

QTL underlying field grain drying rate after physiological maturity in maize (Zea Mays L.)

Abstract: Grain moisture in maize at harvest depends on the grain drying rate (GDR) after physiological maturity. The maize plants with high GDR can reduce grain moisture rapidly, which will shorten the drying time after harvest and prevent the grain to be mildew and enhance maize quality. In this study, A total of 280 recombinant inbred lines that were derived from a cross between Ji846 (high drying rate, 1.18 % day -1 ) and Ye3189 (slow drying rate, 0.39 % day -1 ) were used to construct genetic linkage map and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
(19 reference statements)
1
17
1
1
Order By: Relevance
“…According to the comparative analysis with our study results, preliminary mapping results of qFkdr2b and qFkdr2d detected in our study were consistent with QTLs found by both Stuber et al (1992) and Sala et al (2006). The mapping results of qFkdr3a and qFkdr3c detected in our study also agreed with the QTLs found in previous studies (Ho et al, 2002;Capelle et al, 2010;Wang et al, 2012;Xiang et al, 2012).…”
Section: Introductionsupporting
confidence: 93%
“…According to the comparative analysis with our study results, preliminary mapping results of qFkdr2b and qFkdr2d detected in our study were consistent with QTLs found by both Stuber et al (1992) and Sala et al (2006). The mapping results of qFkdr3a and qFkdr3c detected in our study also agreed with the QTLs found in previous studies (Ho et al, 2002;Capelle et al, 2010;Wang et al, 2012;Xiang et al, 2012).…”
Section: Introductionsupporting
confidence: 93%
“…All these methods are effective, but require precise calibration. The classical oven-drying method, although laborious and time-consuming, is the most reliable way to obtain accurate GWC value [8,26,42,45,57,58]. Considering that the mapping of a small-effect QTL requires extremely accurate GWC values, we finally chose an improved ovendrying method.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar work with 280 RILs, 14 GDR QTL were identified after PM, and each could explain 5.05-16.28% of the total GDR variation. Two of them, qKdr-2-1 and qKdr-3-6, were consistently detected across both locations [45]. With 330 F 2:3 families, 10 GWC at 45 DAP QTL, 10 GWC at harvest QTL and 10 AUDDC (area under the dry down curve) QTL were detected.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is commonly determined only in pre commercial and commercial hybrids, aimed at guiding technicians along with producers. This phenotypic attribute is dependent on the genetic constitution of the genotypes, both during and after physiological maturity, revealing the importance of genetic factors (Wang et al, 2012). However, the selection of elite lines for earliness and yield in breeding hybrids for tropical regions is hampered by the complexity of these traits and negative correlation (Hallauer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%